A new paradigm of investment in human capital in the age of artificial intelligence: a study of the dynamic match between education system reform and labor market demands ("Journal "U". Economy. Management. Finance.", 2025)
This paper investigates the transformation of approaches to human capital investment amidst the Fourth Industrial Revolution. The article analyzes the dual impact of artificial intelligence (AI) on the labor market, which leads to the displacement of some professions and the creation of new ones that demand higher-order cognitive and socio-emotional skills. It substantiates the need to reform the traditional education system, which suffers from inertia and a mismatch with modern requirements. As a solution, a dynamic matching model is proposed, based on close cooperation between the state, business, and educational institutions, the use of big data analysis to forecast skills demand, and the cultivation of a lifelong learning culture. The conclusion asserts that creating a flexible and adaptive system for human capital development is a key factor in ensuring competitiveness and sustainable economic growth in the age of AI.
Keywords: artificial intelligence; human capital; labor market; education system; education reform; professional skills; lifelong learning; dynamic matching; digital transformation; big data analysis